Pengaruh Terapi Bekam Terhadap Penurunan Tekanan Darah Pada Klien Hipertensi - Hengki Irawan; Setyo Ari (Akademi Keperawatan Dharma Husada Kediri, 2012)
Hypertension or high blood pressure is one of the major health problems that require special attention. Cupping therapy is a process to remove dirty blood from the body through the skin surface. Cupping is an alternative to lower blood pressure. The purpose of this study was to determine the effect of therapy bruise to the decrease of blood pressure in hypertensive clients. This research is taking pre-experimental one group pretest-post test design. The sample was selected based on inclusion criteria using accidental sampling with total respondent 14 people. Here is the independent variable and dependent variable bleed therapy is to decrease blood pressure. Collect data by observation. Collecting and using data pengolahahan T test with a significant α ≤ 0.05. The results showed that there was a significant decrease in blood pressure between pre-test and post-test for systolic blood pressure decreased by an average of 22.857 mmHg and pre-test and post-test diastolic blood pressure by an average of 21.429 mmHg and testing with the T test indicates p = 0001 and 0003 (α <0.05). It can be concluded that there are significant bruise therapy to decrease blood pressure in hypertension patients. Doing the right skin bruise location will be on the mast cell, which will produce substances such as serotonin, histamine, bradykinin, slow-reacting substance, Nitric Oxide (NO) and endorphins. These substances will make repairs and reduce the capillary pressure darah.Hasilnya relaxing effect on muscle and vasodilatation of blood vessels, and eventually the blood pressure decrease. Needs further research with more respondents and considers factors - confounding factor in research. With this result can bleed into one alternative way of treatment of hypertension